ANALISIS PENERAPAN TAX REVIEW ATAS PAJAK PERTAMBAHAN NILAI SEBAGAI ALAT UNTUK MENILAI KEWAJIBAN KONTINJENSI PADA RSIA XYZ - Utari, I Gst Ayu Diah; Malini R, Ni Gusti Ayu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.10.NO.06.TAHUN.2021DO - 10.24843/EEB.2021.v10.i06.p06, 2021)
The purpose of this research is to find out the tax review of VAT on RSIA XYZ inaccordance with tax law and to assess and evaluate contingency obligations on tax charges in the form of interest sanctions or tax penalties. The data used in this research is quantitative data. The data source is secondary data. The data is collected using interview, observation and documentation methods. Data analysis techniques used in this research are descriptive quantitative analysis techniques. Based on the description of the results of the study authors conducted a tax review of Value Added Tax (VAT) on RSIA XYZ, it was concluded that taxpayer compliance with tax object with tax rate and tax reporting in accordance with tax rules. But in terms of deposit, RSIA XYZ is not correct in making payments so there is a underpayment of Rp.3,168,679,-. For this underpayment, RSIA XYZ has a contingency obligation of Rp.126,747,-. The amount is obtained from interest sanctions for delays in payment of Outstanding Value Added Tax. So RSIA XYZ can not be said as a compliant taxpayer because there is still a delay in payment of taxes in accordance with tax rules.